A Founder Large Deletion Mutation in Xeroderma Pigmentosum-Variant Form in Tunisia: Implication for Molecular Diagnosis and Therapy. (3rd May 2014) - Ben Rekaya, Mariem; Laroussi, Nadia; Messaoud, Olfa; Jones, Mariem; Jerbi, Manel; Naouali, Chokri; Bouyacoub, Yosra; Chargui, Mariem; Kefi, Rym; Fazaa, Becima; Boubaker, Mohamed Samir; Boussen, Hamouda; et al.
Abstract : Xeroderma pigmentosum Variant (XP-V) form is characterized by a late onset of skin symptoms. Our aim is the clinical and genetic investigations of XP-V Tunisian patients in order to develop a simple tool for early diagnosis. We investigated 16 suspected XP patients belonging to ten consanguineous families. Analysis of the POLH gene was performed by linkage analysis, long range PCR, and sequencing. Genetic analysis showed linkage to the POLH gene with a founder haplotype in all affected patients. Long range PCR of exon 9 to exon 11 showed a 3926 bp deletion compared to control individuals. Sequence analysis demonstrates that this deletion has occurred between two Alu-Sq2 repetitive sequences in the same orientation, respectively, in introns 9 and 10. We suggest that this mutation POLH NG_009252.1: g.36847_40771del3925 is caused by an equal crossover event that occurred between two homologous chromosomes at meiosis. These results allowed us to develop a simple test based on a simple PCR in order to screen suspected XP-V patients. In Tunisia, the prevalence of XP-V group seems to be underestimated and clinical diagnosis is usually later. Cascade screening of this founder mutation by PCR in regions with high frequency of XP provides a rapid and cost-effective tool for early diagnosis of XP-V in Tunisia and North Africa.